Child Marriage in the United States: How Common Is the Practice, And Which Children Are at Greatest Risk?. Issue 2 (17th April 2018) - Koski, Alissa; Heymann, Jody
Abstract : CONTEXT: Marriage before the age of 18, commonly referred to as child marriage, is legal under varying conditions across the United States. The prevalence of child marriage among recent cohorts is unknown. METHODS: American Community Survey data for 2010–2014 were used to estimate the average national and state‐level proportions of children who had ever been married. Prevalence was calculated by gender, race and ethnicity, and birthplace, and the living arrangements of currently married children were examined. RESULTS: Approximately 6.2 of every 1, 000 children surveyed had ever been married. Prevalence varied from more than 10 per 1, 000 in West Virginia, Hawaii and North Dakota to less than four per 1, 000 in Maine, Rhode Island and Wyoming. It was higher among girls than among boys (6.8 vs. 5.7 per 1, 000), and was lower among white non‐Hispanic children (5.0 per 1, 000) than among almost every other racial or ethnic group studied; it was especially high among children of American Indian or Chinese descent (10.3 and 14.2, respectively). Immigrant children were more likely than U.S.‐born children to have been married; prevalence among children from Mexico, Central America and the Middle East was 2–4 times that of children born in the United States. Only 20% of married children were living with their spouses; the majority of the rest were living with their parents. CONCLUSIONS: Child marriage occurs throughout the country. Research on the social forces that perpetuate child marriage is needed to inform efforts to prevent it.